MPEG-5 LCEVC for 3.0 Next Generation Digital TV in Brazil - Ciccarelli, Lorenzo; Ferrara, Simone; Maurer, Florian (Frontiers in Signal Processing, 2022)
TV 3.0 is the next generation digital broadcasting system developed in Brazil by the SBTVD Forum. The ambition of TV 3.0 is significantly higher than that of previous generations as it targets the delivery of IP based signals for applications, such as 8K, HDR, virtual and augmented reality, video enhancement and scalability. To deliver such services, more advanced and flexible compression technologies are required. MPEG-5 Part 2 Low Complexity Enhancement Video Coding (LCEVC) is a new video coding standard which works in combination with a separate video standard (e.g., AVC, HEVC, VVC, AV1) to enhance the quality of a video. In the typical scenario, the enhanced quality is provided in terms of a higher resolution video obtained by adding details coded through an enhancement layer to a lower resolution version of the same video coded through a base layer. The LCEVC format also provides the ability to signal the bit-depth of the base layer independently from that of the enhancement layer and allowing up to 14-bit depth HDR. MPEG-5 LCEVC has been selected by the SBTVD committee as part of the TV 3.0 in December 2021. In this paper we describe the proposal submitted for LCEVC in response to the SBTVD call for proposals for TV 3.0.